Biologically active substances of some species of the genus Lathyrus L. - A. E. Solovyeva; Т. V. Shelenga; M. O. Burlyaeva (Труды по прикладной ботанике, генетике и селекции)
Background. Many of perennial and annual Lathyrus species have economic significance and are used of the world's agriculture. They are often cultivated as forage crops. An important role in developing new forage crops is given to selection for an increased quality of green biomass. Studying biologically active substances (BAS) in green matter of different Lathyrus varieties is needed to search for accessions with as high nutritional value as possible that can serve as sources of BAS.Materials and methods. Thirty-five accessions representing 6 species (L. sativus L., L. vernus (L.) Bernh., L. latifolius L., L. tuberosus L., L. linifolius (Reichard) Bassler, L. sylvestris L.) of the genus Lathyrus L. from the VIR collection were studied. BAS were detected in the green biomass of the accessions in an early phase of bean ripening. The accessions were analyzed by VIR-approved methods (Ermakov et al., 1987). The qualitative and quantitative analyses of phenolic compounds was performed by means of gas chromatography with mass spectrometry (GC-MS Agilent 6850, USA).Results. The content of ascorbic acid, carotenoids, carotenes, в-carotene, chlorophylls a and b, phenolic compounds in the Lathyrus species was studied for the first time. Significant interspecific and intervarietal differences were identified in the BAS content of green matter. The range of variability was as follows: ascorbic acid: 39.0-133.0; chlorophylls a and b: 55.5-365.5; carotenoids: 10.6-44.5; carotenes: 3.630.0; в-carotene: 2.6-24.8; phenols: 4.4-199.4 mg/100g of raw material. The highest rates were observed in L. linifolius and L. latifolius accessions.Conclusion. Green biomass of the studied Lathyrus accessions was balanced in the BAS content and showed high nutritive value. All studied species are of interest for forage crop breeding. The accessions of flat pea (L. sylvestris) and grass pea (L. sativus) are promising for practical use in feed production. L. linifolius and L. latifolius have good prospects as sources of biologically active substances.